Pengaruh Pendapatan Komprehensif Lain Terhadap Nilai Buku dan Harga Saham (Studi Kasus: 44 Perusahaan Tambang yang Terdaftar di Bursa Efek) - Diva Fadillah Ramika; Hanif Hidayatullah; Indri Nazwah; Aditya Fahreza; Ahmad Valevi; Yosep Eka Putra; Mega Rahmi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of Other Comprehensive Income on book value and stock prices of mining sector companies listed on the Indonesia Stock Exchange. Other Comprehensive Income is a component that emerged from the adoption of IFRS-based accounting standards, encompassing items such as revaluation surplus on fixed assets, actuarial gains/losses on defined benefit plans, foreign currency translation differences, and changes in the fair value of certain financial instruments. This component is not recognized in net income, yet it directly affects company equity, potentially providing additional relevant information for investors in assessing firm performance and value. The research sample consists of 46 mining companies listed on the Indonesia Stock Exchange during a specified observation period, selected using the purposive sampling method. Data were analyzed using panel data regression with the assistance of [Eviews/SPSS, adjust as needed] software. The independent variable in this study is Other Comprehensive Income, while the dependent variables are book value per share and stock price. The results show that Other Comprehensive Income has a [significant/insignificant] effect on book value and a [significant/insignificant] effect on stock price. These findings indicate that the market [does/does not] respond to Other Comprehensive Income information in making investment decisions in the mining sector. This study is expected to contribute to investors, company management, and regulators in understanding the value relevance of the Other Comprehensive Income component in the financial statements of mining companies.